Efficient Corncob Biorefinery for Ethanol Initiated by a Novel Pretreatment of Densifying Lignocellulosic Biomass with Sulfuric Acid - Shuangmei Liu; Yang Yu; Zhaoxian Xu; Sitong Chen; Guannan Shen; Xinchuan Yuan; Qiufeng Deng; Wenyuan Shen; Shizhong Yang; Chengcheng Zhang; Xiangxue Chen; Mingjie Jin (Fermentation, 2022)
Corncob is a potential feedstock for biorefineries to produce cellulosic ethanol and other chemicals. Densifying lignocellulosic biomass with chemicals followed by autoclave (DLCA) has been confirmed an efficient and economical pretreatment method, and it was applied in the present work for conversion of corncob to bioethanol. The dosage of sulfuric acid, solid loading of biomass, and autoclave time for pretreatment were investigated. Enzymatic hydrolysis at 25–35% solids loadings resulted in 91–97% sugar conversions. Fermentation of the resulted hydrolysates went well with the highest ethanol titer reaching 75.71 g/L at 35% solid loading. Simultaneous saccharification and co-fermentation was applied to further improve xylose consumption at high solids loadings and the ethanol titer was enhanced to 82.0 g/L at 35% solid loading with an ethanol yield of 21.67 kg/100 kg corncob. This study demonstrated DLCA provided a highly digestible and highly fermentable corncob for biorefinery.